Review Study of Hoax Email Characteristic - Yuliani, SY.; Sahib, Shahrin; Faizal Abdollah, Mohd; Nasser Al-Mhiqani, Mohammed; Rialdy Atmadja, Aldy (International Journal of Engineering and Technology, 2018)
Hoax on email is one form of attack in the cyber world where an email account will be sent with fake news that has many goals to take advantage or raise the rating of sales of a product. A Hoax can affect many people by damaging the credibility of the image of a person or group. The phenomenon of this hoax would cause anxiety in the community and even more bad effects because of the potential for the wrong power of the news or information. In this paper we review the Hoax detection systems, Types of Hoax, and machine learning models that has been used to detect the Hoax. This work serves as a basis for further studies on Hoax detection systems.Â Â
Keywords: Hoax; Fake news; Hoax detection; Hoax detection systems